Pemikiran Pendidikan Islam di Indonesia ( Kh. Ahmad Dahlan dan Kh. Hasyim Asy’ari) - Isnaniatun, Nia; Oktaviani, Sheilla; Pratama, Dian Arif Noor (Madani: Jurnal Ilmiah Multidisiplin, 2024)
K.H. Ahmad Dahlan and K.H. Hasyim Asy'ari, two well-known educational figures in this country, in this article. These two figures work to advance Indonesian Muslims in different ways, but there are clear similarities between them. The results of this study show that it can be concluded that KH Ahmad Dahlan and KH Hasyim Asy'ari are important figures in Indonesian Islamic educational thought, even though each has a different focus. They all agree that Islamic education is very important to change the world. KH Education Concept. Ahmad Dahlan is a valuable legacy for the Indonesian nation. This educational concept is still relevant to the educational context in the modern era and can be a reference for educators in designing and implementing quality and meaningful learning for students. KH Education Concept. Hasyim Asy'ari is a valuable legacy for the Indonesian nation. This educational concept is still relevant to the educational context in the modern era and can be a reference for educators in designing and implementing quality and meaningful learning for students.